Дослідження точності оброблення циліндра різцем із твердого сплаву - Попов, Станіслав Вячеславович; Popov, Stanislav (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: Одним із показників ефективної роботи сучасного металорізального обладнання є точність оброблення. Важливим етапом у технології машинобудування є перехід від застарілих моделей металорі-зальних верстатів до обладнання із числовим програмним забезпеченням. Цього можливо досягти за умови збереження та суттєвого покращення точності оброблення, зокрема розточування отвору твердосплавним різцем у чавунній корпусній деталі.Для оцінювання точності оброблення на металорізальному верстаті із числовим програмним керуванням про-ведено вимірювання розмірних параметрів циліндра. Здійснено статистичне оброблення результатів, яке дозволило зробити висновки щодо необхідності додаткового підналагодження обладнання, а також імовірної кількості браку. /// EN: The accuracy of machining on metal-cutting equipment is one of the main indicators of its efficiency. It is crucial for ensuring the quality of finished products. In the conditions of modern mechanical engineering, an important stage is the transition from outdated models of metal-cutting machines to new technologies. For example, machining on machines with numerical software. Thus, new opportunities open up for increasing the accuracy of machining. This will reduce production costs and improve the competitiveness of products.One of the key tasks that must be solved within the framework of this transition is to ensure high machining accuracy, especially when boring holes with a carbide cutter in a cast-iron body part. The use of a carbide tool allows you to achieve better characteristics during turning. This will also have a positive effect on the accuracy of machining cast-iron products. Nevertheless, to achieve results, it is necessary to conduct a thorough analysis and control of the machining process.To assess the machining accuracy on a CNC machine tool, the cylinder dimensional parameter was measured. This allowed us to collect data on the accuracy of the hole boring and determine deviations from the specified dimensions. The impact of cutting tool wear is considered minimal, so it was not taken into account. Statistical processing of the measurement results helped to draw conclusions about the need for additional equipment adjustment.In addition, the results of the experiment allowed us to estimate the probable number of defects. They can occur during the machining process. Determining the causes of deviations and controlling machining accuracy are critically important for preventing the production of defective parts.Constant monitoring and analysis of machining accuracy is the key to the effective operation of modern metal-cutting equipment and improving the quality of production in general.
Research on the accuracy of cylinder machining with a hard alloy tool
Keywords: металорізальний верстат; зношування; різальний інструмент; статистичне оброблення; допуск; варіаційний ряд; гістограма; момент розподілу; підналагодження; брак продукції; metal-cutting machine; wear; cutting tool; statistical processing; tolerance; variation series; histogram; distribution moment; fine-tuning; processing defect